Resveratrol Increases Cisplatin Sensitivity in Pancreatic Cancer Cells by Modulating Dihydroorotatede Hydrogenase-Mediated Ferroptosis - ZHENG Yanxia, LÜ Siyi, LI Tingting, DING Yusong (Shipin Kexue)
Objective: To investigate the effect of resveratrol (RSV) in increasing the sensitivity of pancreatic cancer cells to cisplatin (DDP) through inhibition of dihydroorotatede hydrogenase (DHODH) and to analyze its potential mechanism of action from the perspective of ferroptosis. Methods: The human pancreatic ductal cancer cell line PANC1 (0, 10, 20, 30, 40, 50, 60, 70, and 80 μmol/L) and the human orthotopic pancreatic cancer cell line BxPC-3 (0, 2, 4, 6, 8, 10, 12, and 14 μmol/L) were treated with different doses of DDP to induce ferroptosis. Subsequently, the effect of intervention with brequinar (BQR) or RSV was explored on DDP-induced ferroptosis in pancreatic cancer cells. To explore the effects of DDP combined with BQR or RSV on ferroptosis-related intracellular molecules, cell viability was determined by the cell counting kit-8 (CCK-8) assay, and Western blot was used to detect the expression levels of glutathione peroxidase 4 (GPX4), recombinant solute carrier family 7 member 11 (SLC7A11 or xCT) and DHODH in cells. The content of malondialdehyde (MDA) was determined spectrophotometrically to evaluate the degree of lipid peroxidation. The level of intracellular reactive oxygen species (ROS) was detected using DCFH-DA probe to further understand the changes of oxidative stress. The fluorescent probe JC-1 was used to detect mitochondrial membrane potential (MMP) to explore the changes of mitochondrial function in cells. Immunofluorescence was used to detect the level of the cell proliferation marker Ki-67 to evaluate the changes of cell proliferation. Results: DDP treatment induced ferroptosis in pancreatic cancer cells (P < 0.05). Both BQR and RSV alone or in combination with DDP significantly decreased the protein expression levels of GPX4, xCT, and DHODH in pancreatic cancer cells (P < 0.05), as well as the levels of MMP and Ki-67 (P < 0.05). In contrast, BQR/RSV treatment elevated the levels of intracellular ROS and MDA (P < 0.05), and the effect was more pronounced in combination with DDP (P < 0.05). Transfection with DHODH adenovirus significantly reversed the inhibitory effect of DDP combined with RSV on the proliferation of pancreatic cancer cells (P < 0.05). Conclusion: DHODH expression is up-regulated in pancreatic cancer tissues. DHODH inhibition promotes ferroptosis and enhances cisplatin sensitivity in pancreatic cancer cells. RSV may act as an inhibitor of DHODH to promote cisplatin-induced ferroptosis in pancreatic cancer cells.